SURVEY OF STAFF OPINIONS ABOUT EXTENDED HAEMODIALYSIS TREATMENT TIME AND SERVICE IMPLICATIONS. Issue 3 (16th March 2015) - Singh, Seema; Procter, Susan; Power, Albert; Pusey, Charles; Choi, Peter; Duncan, Neill; Brown, Edwina
SUMMARY Background We explored the potential impact of staff opinions and service provision upon patient's willingness to recruit to a clinical trial studying the effects of extended treatment time (TT) on haemodialysis (HD), six hours versus four hours for a period of twenty‐four weeks. Methods We conducted a local survey of dialysis nurses and a national survey of multidisciplinary HD staff opinions to extended TT including clinical benefits, tolerance to, prescription and ability to accommodate extended TT on in‐centre HD programmes. Results The survey was completed by 56/134 (42%) local nurses and the national survey by 15/72 (21%) of dialysis providers across the UK (35% nurses and 75% other healthcare professionals). The majority of respondents felt extended TT was clinically beneficial but only 42% of nurses would recommend extended TT compared to 95% of non‐nursing healthcare professionals (p < 0.0001). Although 45% of nurses felt that it was well tolerated, non‐nursing healthcare professionals suggested this was significantly higher at 75% (p < 0.05). The negative impact on service provision was agreed by 83% of nurses with the need to facilitate shifts within a finite time period and pressure to find session spaces being cited. Conclusion There is conflict between the understanding that extended TT is clinically beneficial and its prescription & delivery to patients. Enrolment to studies examining HD delivery strategies may be influenced by service provision and staff attitudes. In centre HD has been designed to maximise patient throughput and we may need to consider more flexible settings in which to deliver longer treatment time: Home HD maybe a solution.